Equilibrium Search and the Impact of Equal Opportunities for Women - Melvyn G. Coles; Marco Francesconi (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper develops a new equilibrium model of two-sided search where agents have multiple attributes and general payoff functions. The model can be applied to several substantive issues. Here we use it to provide a novel understanding of the separate effects of equal opportunities for women in the labor market and improved contraception on female education, employment, and timing of first births after World War II. We find that the diffusion of the pill might have played an important role in explaining the observed rise in female education and employment since the 1960s. But without equal opportunities, these changes would have not occurred.
Keywords: C60; J00; J10; N30; 330; two-sided search; marriage; female labor supply; pill; age at first birth